Handbook of olfaction and gustation - Doty, Richard L. (Wiley Blackwell, 2015)
"The largest collection of basic, clinical, and applied knowledge on the chemical senses ever compiled in one volume, the third edition of Handbook of Olfaction and Gustation encompass recent developments in all fields of chemosensory science, particularly the most recent advances in neurobiology, neuroscience, molecular biology, and modern functional imaging techniques. Divided into five main sections, the text covers the senses of smell and taste as well as sensory integration, industrial applications, and other chemosensory systems. This is essential reading for clinicians and academic researchers interested in basic and applied chemosensory perception"--Provided by publisher.